Potentiation of Brain Mitochondrial Function by S-equol and R/S-equol Estrogen Receptor β Selective PhytoSERM Treatments - Yao, Jia (2013)
Previously we developed an estrogen receptor β-selective phytoestrogenic (phytoSERM) combination, which contains a mixture of genistein, daidzein, and racemic R/S-equol. The phytoSERM combination was found neuroprotective and non-feminizing both in vitro and in vivo. Further, it prevented or alleviated physical and neurological changes associated with human menopause and Alzheimer’s disease. In the current study, we conducted translational analyses to compare the effects of racemic R/S-equol-containing with S-equol-containing phytoSERM therapeutic combinations on mitochondrial markers in rat hippocampal neuronal cultures and in a female mouse ovariectomy (OVX) model. Data revealed that both the S-equol and R/S-equol phytoSERM treatments regulated mitochondrial function, with S-equol phytoSERM combination eliciting greater response in mitochondrial potentiation. Both phytoSERM combination treatments increased expression of key proteins and enzymes involved in energy production, restored the OVX-induced decrease in activity of key bioenergetic enzymes, and reduced OVX-induced increase in lipid peroxidation. Comparative analyses on gene expression profile revealed similar regulation between S-equol phytoSERM and R/S-equol phytoSERM treatments with minimal differences. Both combinations regulated genes involved in essential bioenergetic pathways, including glucose metabolism and energy sensing, lipid metabolism, cholesterol trafficking, redox homeostasis and β-amyloid production and clearance. Further, no uterotrophic response was induced by either of the phytoSERM combinations. These findings indicate translational validity for development of an ER β selective S-equol phytoSERM combination as a nutraceutical to prevent menopause-associated symptoms and to promote brain metabolic activity.